Docosahexaenoic Acid Inhibits Inflammation-Induced Osteoclast Formation and Bone Resorption in vivo Through GPR120 by Inhibiting TNF-α Production in Macrophages and Directly Inhibiting Osteoclast Formation - Kishikawa, Akiko; Kitaura, Hideki; Kimura, Keisuke; Ogawa, Saika; Qi, Jiawei; Shen, Wei-Ren; Ohori, Fumitoshi; Noguchi, Takahiro; Marahleh, Aseel; Nara, Yasuhiko; Ichimura, Atsuhiko; Mizoguchi, Itaru (Frontiers in Endocrinology, 2019)
Docosahexaenoic acid (DHA) is an n-3 fatty acid that is an important structural component of the cell membrane. DHA exerts potent anti-inflammatory effects through G protein-coupled receptor 120 (GPR120), which is a functional receptor for n-3 fatty acids. DHA also regulates osteoclast formation and function. However, no studies have investigated the effect of DHA on inflammation-induced osteoclast formation in vivo. In the present study, we investigated whether DHA influences osteoclast formation, bone resorption and the expression of osteoclast-associated cytokines during lipopolysaccharide (LPS)-induced inflammation in vivo, and then we elucidated the underlying mechanisms by using in vitro experiments. In vitro experiments revealed both receptor activator of NF-kB ligand (RANKL)- and tumor necrosis factor-α (TNF-α)-induced osteoclast formation was inhibited by DHA. Supracalvarial administration of LPS with or without DHA was carried out for 5 days and then the number of osteoclasts, ratio of bone resorption pits and the level of type I collagen C-terminal cross-linked telopeptide were measured. All measurements were significantly lower in LPS+DHA-co-administered mice than LPS-administered mice. However, this DHA-induced inhibition was not observed in LPS-, DHA-, and selective GPR120 antagonist AH7614-co-administered mice. Furthermore, the expression of RANKL and TNF-α mRNAs was lower in the LPS+DHA-co-administered group than in the LPS-administered group in vivo. TNF-α mRNA levels were decreased in macrophages co-treated with LPS+DHA compared with cells treated with LPS in vitro. In contrast, RANKL mRNA expression levels from osteoblasts co-treated with DHA and LPS in vitro were equal to that in cells treated with LPS alone. Finally, the inhibitory effects of DHA on osteoclast formation in vitro were not observed by using osteoclast precursors from GPR120-deficient mice, and inhibition of LPS-induced osteoclast formation and bone resorption by DHA in vivo was not observed in GPR120-deficient mice. These results suggest that DHA inhibits LPS-induced osteoclast formation and bone resorption in vivo via GPR120 by inhibiting LPS-induced TNF-α production in macrophages along with direct inhibition of osteoclast formation.